Analisis Pengelolaan Kas pada UMKM Batik di Kabupaten Cirebon - Fini Iisyatirroodliyah Henuari; Mohammad Taufik Aziz; Mery Sukartini2 (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to analyze cash management practices in Batik MSMEs in Cirebon Regency using a qualitative approach that combines direct observation and in-depth interviews with business owners. The study found that most Batik MSMEs still rely on manual cash management systems, which ultimately poses various challenges, particularly in terms of unstructured financial recording and minimal cash flow planning. This condition makes it difficult to communicate receipts and expenditures in real time, potentially leading to errors in fund management and disrupting business financial stability. Furthermore, the study revealed variations in cash receipt recording methods, such as daily or weekly recording, which are inconsistent across MSMEs. This impacts transparency and effective financial control. The lack of thorough cash flow planning also makes it difficult for business owners to deal with insufficient liquidity, especially when there is a surge in sales or sudden needs. As a result, some MSMEs experience problems meeting their payment obligations on time, including to suppliers and employees. The findings of this study highlight the importance of financial literacy education for Batik MSMEs so they can understand the basic concepts of cash management well. Furthermore, the use of digital technology, such as simple financial recording applications, is highly recommended to improve efficiency and accuracy in cash flow management. This technology implementation is expected to assist MSMEs in making more informed financial decisions and supporting the long-term sustainability of their businesses. Therefore, this study provides strategic recommendations for local governments and MSME support institutions to provide adequate training and technological facilities to strengthen financial management capacity in the batik MSME sector in Cirebon Regency.